IMPROVING VOCABULARY MASTERY THROUGH SEGONG GAME FOR FIRST-GRADE STUDENTS AT ALOK PUBLIC JUNIOR HIGH SCHOOL - Ahmad, Fatmawati Suaebas; Sadin, Maria Louise Aprillia Lidia; De Rosari, Vinsensia Yosefa (Ma Chung Press, 2023)
Vocabulary proficiency plays a vital role in English language acquisition, enabling individuals to comprehend written texts and effectively articulate their ideas in oral and written communication. This article presents an academic study that focuses on enhancing the vocabulary competency of first-grade students through the implementation of traditional Segong activities. The research was conducted in the context of Alok Public Junior High School during the academic year 2022/2023. This study reexamines the efficacy of employing specific Segong traditional games as a strategy to facilitate the development of English vocabulary among students in an educational setting. The Segong game format was utilized to enhance students' vocabulary knowledge while harnessing the teacher's instructional prowess. The research employed a two-cycle classroom action research methodology, incorporating assessments, questionnaires, and observations to gather data. The findings reveal a substantial improvement in vocabulary mastery, as evidenced by an initial data analysis showing a percentage increase of 18% in the pre-cycles. Notably, the first cycle demonstrated a growth rate of 63%, while the second cycle witnessed a remarkable increase of 85.72%. These outcomes affirm the effectiveness of the Segong game in enhancing English vocabulary acquisition